The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijerph16234705
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices Regarding Dengue Fever among Pediatric and Adult In-Patients in Metro Manila, Philippines

Abstract: Background: Knowledge, attitude, and practice (KAP) of in-patients with dengue fever (DF) through hospital-based surveillance has not been done. This study aimed to assess and compare the KAP, identify its predictors, correlation, and protective factors among pediatric and adult patients with DF and community-based controls to structure proactive community-wide DF prevention and control programs. Methods: This case-control study involved clinically or serologically confirmed patients (pediatrics n = 233; adult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
2
20
1
Order By: Relevance
“…Opposite to the results of our previous study which found that as the age of pediatric patients with DF increased, their attitude towards DF decreased [58], this present study found that as their age increased, their anxiety also increased. Thus, their knowledge about their disease, rather than their attitude towards it, may explain this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…Opposite to the results of our previous study which found that as the age of pediatric patients with DF increased, their attitude towards DF decreased [58], this present study found that as their age increased, their anxiety also increased. Thus, their knowledge about their disease, rather than their attitude towards it, may explain this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the overall mean percentage scores of 52%, 69.2% and 71.4% for KAP was higher than a hospital-based study that examined KAP on dengue fever among paediatric and adult in-patients in Metro Manila, Philippines [ 34 ]. This suggests that people in Dhaka were generally more knowledgeable, concerned, and had better practices towards dengue than in the comparison study [ 34 ].…”
Section: Discussionmentioning
confidence: 60%
“…KAP surveys relating to dengue have been carried out in many countries, including a number in Latin America. [15][16][17][18][19][20][21][22][23] MINSA carried out a survey in 2004 reporting how KAP can influence the successful implementation of public health campaigns. 24 Since then, they have carried out numerous campaigns to promote and educate the public in relation to dengue and other A. aegypti transmitted diseases.…”
Section: Open Accessmentioning
confidence: 99%